PENGARUH PENERAPAN MODEL THINK TALK WRITE TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPTIF SISWA - AP, Nurfaizah; Latri, Latri; Juwaria, Juwaria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effect of implementing the think talk write learning model on the descriptive essay writing skills of class IV UPT SD Inpres Karunrung Makassar City students. The type of research used is quantitative research using Quasi Experiment. This research uses Nonequivalent Control Group Design which involves two research groups, namely the experimental class and the control class. The experimental class is the class that receives treatment, while the control class is the class that does not receive treatment. Determining the sample in this study used purposive sampling, so that 18 students were obtained from class IVA as the experimental class and 18 students from class IVB as the control class. The data collection tool used is a written test by paying attention to the assessment aspects. The data analysis technique used is the independent sample t-test to test whether there is a significant difference between the two variances. Based on the results of data analysis using the Independent Sample t-test, with a pre-test value of 0.162 and a post-test of 0.000, it can be concluded that there is a significant influence from implementing the think talk write model on students' writing skills.